Clinicopathological and prognostic significance of elevated BTF3 expression in gastric cancer: BTF3 expression in gastric cancer - Zhang, Pu; Wang, Chaochen; Wang, Haiqing; Zhang, Xiuzhong (Cellular and Molecular Biology, 2023)
The purpose of this paper was to explore the significance of basic transcription factor 3 (BTF3) in the process and clinicopathological parameters of gastric cancer (GC) patients. GC tissues were collected in our hospital to detect the mRNA expression of BTF3 by quantitative real-time polymerase chain reaction (Q-PCR). Western blot analysis was performed to detect the protein expression of BTF3. Kaplan-Meier method and Log-rank analysis were used to analyze the progression-free survival time and overall time of GC patients, while the Chi-square test was used to investigate the association between BTF3 and clinicopathological parameters of GC patients. SiRNA was designed to suppress the expression of BTF3. MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) assay and transwell assay were conducted to determine the viability and invasion ability of GC cells. BTF3 was found abnormally up-regulated in GC tissues and cells and was related to the Grade, Lymph node metastasis and stage of GC patients, as well as the poor progression-free survival and overall survival of them. Besides, inhibition of BTF3 in GC cells could trigger the reduction of cell viability and invasion ability. Our results demonstrated that BTF3 played an important role in the process of GC and could be regarded as a new target for the diagnosis and therapy of GC.